2012
DOI: 10.3813/aaa.918554
|View full text |Cite
|
Sign up to set email alerts
|

What is the Definition for the French Word <I>calme</I> in the European Directive Related to “Quiet Areas”? A Lexicographic Study from the 16th Century Until Today

Abstract: This paper presents al exicographic study of the expression "quiet areas" and its translations as theya ppear in the European directive 2002/49/EC. The main part of this study is about the French translation of "quiet areas": "zones calmes" and focuses on the definition of the word calme.T he analysis conducted in this article is based on various methodologies: diachronic studies and analyses of the lexical field. Those methodologies allowhighlighting the manifold notions linked to the word calme.The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The statements were chosen based on the earlier lexicographic studies [24]. In a survey, participants placed the statements into a pyramid with an 11-point scale from "mostly disagree" (−5) to "mostly agree" (+5).…”
Section: Methodology Of Extractionmentioning
confidence: 99%
“…The statements were chosen based on the earlier lexicographic studies [24]. In a survey, participants placed the statements into a pyramid with an 11-point scale from "mostly disagree" (−5) to "mostly agree" (+5).…”
Section: Methodology Of Extractionmentioning
confidence: 99%
“…Even though there are similarities in how people in different parts of the world perceive the acoustic environment, the connotative meaning of words, and linguistic nuances differ from one language or culture to another [3,7,22,23]. For example, there are two different Spanish versions of the Swedish Soundscape-Quality Protocol; one for Spain and one for Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…The translation of the term (and that of several related perceptual attributes/adjectives) is part of an ongoing debate in international research networks [33,34]. The analysis of the geographical distribution of the mentions (discussed in Section 4.2) revealed that most of them come from English-speaking countries, but several other regions are represented too.…”
Section: Methodology For the Review Of Soundscape Literature In Non-amentioning
confidence: 99%